2017
DOI: 10.1089/vbz.2016.2071
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization ofLeishmaniaParasites in Giemsa-Stained Slides from Cases of Human Cutaneous and Visceral Leishmaniasis, Eastern Algeria

Abstract: Distribution of leishmaniasis in Eastern parts of Algeria, besides finding of L. tropica in the far North, is in this study described for the first time using molecular tools, thus confirming the usefulness of slides for PCR identification of Leishmania parasites in retrospective epidemiological investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…In our study the highest number of specific positive results (highest sensitivity) were observed when PCR amplification was performed on DNA extracted from direct slides for both FTG and CL. These results show concordance with data published by other investigators[41,42].…”
Section: Discussionsupporting
confidence: 94%
“…In our study the highest number of specific positive results (highest sensitivity) were observed when PCR amplification was performed on DNA extracted from direct slides for both FTG and CL. These results show concordance with data published by other investigators[41,42].…”
Section: Discussionsupporting
confidence: 94%
“…Optimal sampling, storage and transport to a receiving laboratory (such as the Centres for Disease Control and Prevention, US, or Fiocruz, Brazil) is critical. Before detection, DNA must first be extracted and purified; this is often performed by using commercial kits, such as the silica-based DNeasy Blood and Tissue Kit (Qiagen, Germany), NucliSENS easyMAG system (BioMerieux, France) or via in-house extraction protocols based on phenol extraction and ethanol precipitation [ 36 , 140 , 141 ]. Some rapid extraction methods have been developed recently, e.g., SpeedXtract (Qiagen, Hilden, Germany), which greatly reduce the time to test result [ 142 ].…”
Section: Methods For the Detection And Diagnosis Of Leishmaniasismentioning
confidence: 99%
“…The use of PCR to detect leishmanial DNA in Giemsa-stained smear scrapings can be used in investigations of the reservoir hosts and in research conducted with infected animal models 9 and therefore, this technique can be applied in Sri Lanka to identify the reservoir hosts. A previous study conducted by Beldi et al, (2017) 10 has confirmed the usefulness of slides for PCR identification of Leishmania parasites in retrospective epidemiological investigations. 10 Therefore, this method can be adopted for similar studies conducted in Sri Lanka.…”
Section: Limitations Of the Present Study And Future Directionsmentioning
confidence: 65%
“…A previous study conducted by Beldi et al, (2017) 10 has confirmed the usefulness of slides for PCR identification of Leishmania parasites in retrospective epidemiological investigations. 10 Therefore, this method can be adopted for similar studies conducted in Sri Lanka.…”
Section: Limitations Of the Present Study And Future Directionsmentioning
confidence: 65%